An investigation on the use of gerunds in students' academic writing at IIUM - Norazah Md. Idrus (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
To possess grammatical ability is one of the many essential assets in language learning and this ability is indispensable in academic writing at tertiary level. It is commonly assumed that tertiary level students would have attained a certain level of grammatical acquisition in academic writing as grammatical incompetence impacts students' performance negatively in delivering their ideas and opinions. Thus, to achieve good scores in academic essays, the use of nominalisation, especially gerunds, is crucial. This study sought to investigate the use of gerunds in students' academic writing at the IIUM. This qualitative study investigated the use of gerunds in academic essays written by students undertaking EAW course in the IIUM. In doing so, this study intended to explore the use of gerunds, determine its functions and to examine its difference(s) in academic essays of high and low scores. Gerunds, being one of the linguistic features in English grammar, is the focal point for this study. Data collected were from EAW students' academic essays, which form part of their course assessments. It was later analysed using textual or linguistic analysis based on the framework of Seiss' (2008). The findings revealed that on average, the use of gerunds in one academic essay of about 300 words was very minimal (two) gerunds used. In total, 260 gerunds were found in a sample of 100 academic essays. Another finding revealed that EAW students used all functions of gerunds except It-Replacement function. Additionally, this study unfolded that academic essays of high scores had more instances of gerunds and more types of functions in comparison to academic essays of low scores. These findings can become exemplary to the understanding of the use of gerunds (or lack of it) in academic essays among IIUM students. These findings offer a better teaching insight to grammar teachers and writing instructors. This study provides a crucial implication on the teaching of academic writing at the tertiary level, especially to the writing instructors, curriculum designers and material developers in creating effective writing courses that give weight and depth to gerunds. Keywords: Gerunds, Lexical Functional Grammar (LFG), Academic Essays.